Evaluasi dan Perancangan Sistem Ventilasi Pada Lubang Tambang Batubara BT 03 Site Bukit Tambun, PT. Nusa Alam Lestari, Desa Salak, Kecamatan Talawi, Kota Sawahlunto - Naufal Deya Al Mafaza Mufti; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2022)
PT. Nusa Alam Lestari is an underground coal mining company located in Salak Village, Talawi District, Sawahlunto City, West Sumatra. Ventilation system on hole BT 03 PT. Nusa Alam Lestari uses a blowing system. This study aims to evaluate the quality and quantity of underground mining based on Ministerial Decree No. 555.K/26/M.PE/1995 with the parameters to be measured including the value of effective temperature, relative humidity, gas content, air requirements for tools, workers and equipment. gas control and measure the speed of the air flowing to get the value of the incoming air discharge. At hole BT 03 there are two forward fronts and six active mining branches. The results of the average temperature measurement on all working fronts of the BT 03 hole are 29.20C and the results of the average humidity measurement are 89.6%. This temperature value has passed the threshold set between 180C-270C and the humidity has also passed the set threshold of 85%. From the results of the calculation of the air quantity, it is also known that the incoming air has a discharge of 2.83 m3/s. In fact, the need for air which includes the need for air for workers, the need for equipment air, and the need for diluting methane gas is 5.0546 m3/s. Based on the situation the ventilation design for the future is to make a through hole from the C8 branch to the surface. In addition, it will also be equipped with a suction blower system. The simulation results using the Ventsim software stated that the intake air flow rate increased to 12.6 m3/s and has met the total air requirement standard. Furthermore, in the design of air ventilation for mining activities for the next 12 months, it is known that the total mining progress is 2345.3 m per year and the production target is 1334 tons per month. To meet the demand for air, a 20-inch centrifugal blower will be used in each hole A and B and 12 axial blowers will be used to help air reach the work front at each branch.